Genetic polymorphisms associated with circadian rhythm dysregulation provide new perspectives on bipolar disorder. (13th February 2018) - Oliveira, Thomaz; Marinho, Victor; Carvalho, Valécia; Magalhães, Francisco; Rocha, Kaline; Ayres, Carla; Teixeira, Silmar; Nunes, Monara; Bastos, Victor Hugo; Pinto, Giovanny R
Abstract: Objectives: The objective of this study was to present a broad view of how genetic polymorphisms in genes that control the rhythmicity and function of circadian rhythm may influence the etiology, pathophysiology and treatment of bipolar disorder (BD). Methods: A bibliographic search was performed to identify and select papers reporting studies on variations in circadian genes and BD. A search of Medline, Google Scholar, Scopus, and Web of Science was carried out to review the literature. Results: Several studies provide evidence of contributions of variations in circadian genes to disease etiology, pathophysiological variations and lithium drug response. Dysfunction of the sleep‐wake cycle, an important brain function regulator, is indicated as the primary means by which circadian gene variations act in mood disorders. Conclusions: Investigations of the effects of circadian genes have suggested that the chronotype offers hope for guiding and improving management of patients with BD. However, BD is a disease of a complex nature and presents multiple endophenotypes determined by different associations between genetics and the environment. Thus, new genomic studies to delimit variations that may help improve the clinical condition of these patients are extremely important.